Stress incontinence combined score (SICS): A novel combined grading system to assess the severity of stress urinary incontinence in women. (November 2022) - Reddy, Deepa; Zulfeen, Momina; Pandey, Deeksha
Abstract: Introduction: Natural history of urinary incontinence (UI) in women is a less understood domain. Stratifying severity of stress urinary incontinence (SUI) can be an important tool to understand the natural history, prognosticate the disease and plan optimal management. Present study was aimed to test a novel score (Stress Incontinence Combined score: SICS) with the currently popular tools International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-UI SF) and Incontinence Symptom Index (ISI) scores. Material and methods: This was a prospective study conducted at a university teaching hospital, over a period of 2 years. After screening women for SUI, SICS was administered. The novel SICS score was then compared with ICIQ-UI SF and ISI. Results: A total of 1750 women, attending various OPDs in a tertiary care hospital, were screened for urinary incontinence. The prevalence of UI and SUI was 26.6% and 12.8% respectively. The agreement between ISI and SICS was 81.7%, while the ICIQ- UI SF agreed with the SICS in 80.8% of the cases. AUROC analysis done showed that a score of 10 or more on the SICS (total score 16) could diagnose high-grade SUI with a sensitivity of 97%, specificity of 96% (Reference: ISI), and a sensitivity of 100%, and specificity of 93% (Reference: ICIQ- UI SF) Conclusion: SICS is the first of its kind tool, developed to specifically grade the severity of SUI, while incorporating both subjective and objective measures, with excellent reliability and reproducibility.